2008
DOI: 10.1002/hyp.6923
|View full text |Cite
|
Sign up to set email alerts
|

Reply to comment on ‘C.‐P. Tung, N.‐M. Hong, C.‐H. Chen, and Y.‐C. Tan. 2004. Regional daily baseflow prediction. Hydrological Processes 18: 2147–2164’

Abstract: The recession analysis introduced by Brutsaert and Nieber (1977) has been applied in many studies. Tung et al. (2004) stated that using time-averaged flows to estimate coefficients for recession equations may result in bias. The reasons include improper time interval to estimate averaged flows and the coefficient a in the recession analysis depends on the initial water table. The latter implies that the coefficient a may be different for different recession events. Rupp and Woods (2008) commented that the bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 4 publications
0
10
0
2
Order By: Relevance
“…Aspirin inhibits the enzyme activity of cyclooxygenase (COX), which affects the generation of prostaglandins (PGs), thereby inhibiting inflammation (Bindu et al, 2020). At the same time, aspirin also has an antioxidative stress effect, which can prevent oxidative damage (Chen et al, 2020;Paseban et al, 2019). Therefore, aspirin may affect PD by influencing these two factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspirin inhibits the enzyme activity of cyclooxygenase (COX), which affects the generation of prostaglandins (PGs), thereby inhibiting inflammation (Bindu et al, 2020). At the same time, aspirin also has an antioxidative stress effect, which can prevent oxidative damage (Chen et al, 2020;Paseban et al, 2019). Therefore, aspirin may affect PD by influencing these two factors.…”
Section: Discussionmentioning
confidence: 99%
“…TXA2 (Majithia & Bhatt, 2019). Aspirin also exhibits anti-inflammatory (Bindu et al, 2020) and antioxidant effects (Chen et al, 2020;Paseban et al, 2019) and has been suggested to be beneficial for PD in some studies (Gabbert et al, 2022;Rangasamy et al, 2019;San Luciano et al, 2020). Cilostazol can increase the expression of Nurr1 in mice, protecting the integrity of dopaminergic neurons and reducing inflammation by suppressing NF-κB and its downstream effectors TNF-α and IL-1β (Hedya et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…150 Preparation of MIPs can be achieved via several methods, including suspension, emulsion, and solgel formation. 151,152 Importantly, many of these procedures are single-step reactions with high yields and will also determine whether the resulting structure is self-supported or must act as a supported membrane. 152,153 Although the variety of available preparative techniques yields exceptional customization capabilities in flux capacity and surface functionality, the synthesis parameters are most commonly obtained experimentally.…”
Section: Synthetic Polymersmentioning
confidence: 99%
“…151,152 Importantly, many of these procedures are single-step reactions with high yields and will also determine whether the resulting structure is self-supported or must act as a supported membrane. 152,153 Although the variety of available preparative techniques yields exceptional customization capabilities in flux capacity and surface functionality, the synthesis parameters are most commonly obtained experimentally. The result is a time-consuming and laborious optimization path, which has so far been the major roadblock to greater MIP advocacy and application.…”
Section: Synthetic Polymersmentioning
confidence: 99%
“…In recent years, LEDs have attracted considerable interest for various applications in liquid crystal display (LCD) backlighting units, traffic signals, and solid-state lighting (SSL). [1][2][3] Further improvements in power handling and light extraction are required for the development of high-power LEDs with a high luminous/wall-plug efficiency. However, the light extraction efficiency of LEDs has significantly deteriorated owing to the problem of total internal reflection (TIR), [4][5][6] which arises from the large difference in refractive indices between GaN (n ¼ 2:5) and air (n ¼ 1).…”
Section: Introductionmentioning
confidence: 99%